Detection of multidrug-resistant methicillin-resistant Staphylococcus aureus from healthy black Bengal goat in Bangladesh - Biswas, Sarbani; Islam, Md. Ariful; Islam, Jahidul; Khatun, Mst. Minara; Rahman, Md. Zaminur (The Journal of Infection in Developing Countries, 2024)
Introduction: The emergence of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) is a growing public health concern. The objective of this study was to determine the prevalence and multi-drug resistant (MDR) profiles of MRSA in goats in Bangladesh. Methodology: A total of 150 samples from goats comprised of rectal swab (n = 50), nasal swab (n = 50), and milk (n = 50) were collected. Isolation of S. aureus from samples was conducted onto mannitol salt agar (MSA). Identification of S. aureus was performed by cultural characteristics, Gram staining, biochemical tests (catalase, coagulase, indole, methyl red, and Voges-Proskaur), and nuc gene-specific PCR assay. The MRSA was identified by cefoxitin disc diffusion test and mecA gene-specific PCR assay. The MDR profiles of MRSA were performed against ampicillin, amoxicillin, gentamicin, cefoxitin, vancomycin, azithromycin, cefotaxime, ciprofloxacin and nalidixic acid by disc diffusion method. Results: The overall prevalence of S. aureus was 35.3% and MRSA was 7.3%. The prevalence of MRSA was 12% in rectal swabs, 8% in nasal swabs, and 2% in milk. The highest resistance of MRSA was against ampicillin (91%) followed by azithromycin (55%), amoxycillin (36%), nalidixic acid (27%), ciprofloxacin (18%) and cefotaxime (9%). Most MRSA isolates (90.9%) exhibited resistance to at least three classes of antibiotics and were MDR. Conclusions: This study shows that goats may harbor MDR-MRSA, posing a risk to public health.